eCM 2002
DOI: 10.22203/ecm.v004a01
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast and osteoblast adhesion and morphology on calcium phosphate surfaces

Abstract: Implant loosening in bone fixation is an unresolved complication associated with internal fixation. It is generally accepted that this problem can be overcome by modifying the implant/bone interface for improved osseointegration. This is achieved, in part, by hydroxyapatite (HA) or tricalcium phosphate coatings. Unfortunately, the benefits of these coatings are constrained by not only the generally low strength of their adhesion to the implant surface but also the limited cohesion within their layers. Anodic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 36 publications
5
96
0
2
Order By: Relevance
“…3C, D) increased with increasing stiffness gels by 7.8 and 6.4 times, respectively. It has been shown that osteoblasts and fibroblasts prefer stiffer surfaces for proliferation [38][39][40] and according to the proliferation data obtained via the cell titer blue kit, we saw that the 0.5% (w/v) genipin crosslinked hydrogel group showed significantly higher rates of cellular proliferation ( p < 0.05, n = 3) over 24 h for osteoblasts and fibroblasts.…”
Section: Cellular Proliferationsupporting
confidence: 57%
“…3C, D) increased with increasing stiffness gels by 7.8 and 6.4 times, respectively. It has been shown that osteoblasts and fibroblasts prefer stiffer surfaces for proliferation [38][39][40] and according to the proliferation data obtained via the cell titer blue kit, we saw that the 0.5% (w/v) genipin crosslinked hydrogel group showed significantly higher rates of cellular proliferation ( p < 0.05, n = 3) over 24 h for osteoblasts and fibroblasts.…”
Section: Cellular Proliferationsupporting
confidence: 57%
“…3A,B,D,E). The thin sections revealed that the lobulated osteoblast-like SaOS-2 cells (Baxter et al, 2002) from untreated cells contained only a low number of mitochondria (Fig. 3A,B), whereas those cells that had been exposed to aCa-polyP-NP contained dense clusters of mitochondria ( Fig.…”
Section: Mitochondria Abundance Increases In Saos-2 Cells After Incubmentioning
confidence: 99%
“…All of the adherent cells over the modified substrate respond to the cell viability, growth rate, and proliferation. [18][19][20] In this study, we describe the correlation between the cell's response and the surface properties. We used different model surfaces with different degrees of wettability and microstructures to examine their influence on the adhesion and proliferation of cells.…”
Section: 12mentioning
confidence: 99%